Factors associated with quality of life in mastectomized patients - Medina-Bueno, Gonzalo A. (2020)
Objetives To determine whether the variables: age, marital status, employment status, level of education, socioeconomic status, disease status, commitment to manual dominance, comorbidity and adjuvant therapy, factors associated with the quality of life in mastectomized patients. Methods It is a cross-sectional observational study, which assesses the quality of life by applying the SF-36 questionnaire, which includes mastectomized women with a diagnosis of breast cancer, unilateral, operated during the period of 2010-2014, sometimes a modified radical mastectomy type Madden , who went to a control by an external office of Oncological Gynecology; who finished adjuvant treatment (chemotherapy and / or radiotherapy), and remain in outpatient control Results The dimensions of the SF-36 in the dimensions of physical health and mental health were similar for the variables: age (<50 and> 50 years), socioeconomic status and manual commitment. They were often older for patients in married marital status, unemployed employment status, secondary education, absent comorbidity, mixed adjuvant therapy, and in curative disease status, when applying Student's t-test and ANOVA (p <0.05) . Conclusions The assessment of the quality of life in mastectomized patients is not associated with age, compromise of manual dominance, or socioeconomic status; The best quality of life is associated with married marital status, unemployed employment status, level of secondary education, absent comorbidity and the status of curative disease.